Aplikasi Pengenalan Jenis Penyakit Ayam dan Cara Pengobatan Berbasis Augmented Reality - Ragil Aris Nurmanto; Zakariyah, Muhammad (STMIK Budi Darma, 2024)
Chicken disease is a problem that is often faced by breeders. The impact of the disease in chickens if handled late will result in fatal things for chickens and become one of the factors of death in chickens. Augmented reality is a technology that is developing now, this technology is currently being widely used as a learning medium that uses interesting and interactive 3d objects. This application is made through several steps, namely, analysis and design, system design, interface design. The application we created aims to be able to overcome problems among farmers and the general public related to recognizing the types of diseases in chickens and how to treat them. The method used in this test is blackbox testing which focuses on testing every function of the button or button in the application, so that it is known whether the buttons are appropriate or not with the expected output results. So the results of testing the black box unit in the application designed in this study all buttons can function properly. So that we get final result in the form of an application for the introduction of chicken disease types and treatment methods based augmented reality, which can be used easily and interactively.